EMOTIONAL INTELLIGENCE AS AN IMPORTANT INTEGRAL CHARACTERISTICS OF CREATIVE PERSONALITY (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the notions "emotional intelligence" the basic theories of forming emotional intelligence, its peculiarities and structural components are revealed.
Keywords: creative personality; emonational intelligence; structural components